(–)–Corydalmine from Corydalis chaerophylla Growing in Nepal - Jha, R. N. (Journal of Nepal Chemical Society, 2010)
(–)–Corydalmine was isolated from the roots of Corydalis chaerophylla and identified by spectral analysis. Keywords: (–)–corydalmine, Corydalis chaerophylla DOI: 10.3126/jncs.v25i0.3309 Journal of Nepal Chemical Society Volume 25, 2010 pp 89-92